2014
DOI: 10.1039/c4nr01607f
|View full text |Cite
|
Sign up to set email alerts
|

A facile green antisolvent approach to Cu2+-doped ZnO nanocrystals with visible-light-responsive photoactivities

Abstract: An environmentally benign antisolvent method has been developed to prepare Cu(2+)-doped ZnO nanocrystals with controllable dopant concentrations. A room temperature ionic liquid, known as a deep eutectic solvent (DES), was used as the solvent to dissolve ZnO powders. Upon the introduction of the ZnO-containing DES into a bad solvent which shows no solvation to ZnO, ZnO was precipitated and grown due to the dramatic decrease of solubility. By adding Cu(2+) ions to the bad solvent, the growth of ZnO from the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…A more visible difference can be found in the temporal decay profiles of OCVDs. The decay traces for both samples was fitted with a biexponential function having time constants of τ 1 and τ 2 . These constants for the bare sample were 2.7 s and 92.7 s, whereas those for the plasmonic photoanode are 1.9 s and 44.6 s. The shorter lifetime could be attributed to band‐to‐band recombination as similar constants were obtained for both samples.…”
Section: Resultsmentioning
confidence: 63%
“…A more visible difference can be found in the temporal decay profiles of OCVDs. The decay traces for both samples was fitted with a biexponential function having time constants of τ 1 and τ 2 . These constants for the bare sample were 2.7 s and 92.7 s, whereas those for the plasmonic photoanode are 1.9 s and 44.6 s. The shorter lifetime could be attributed to band‐to‐band recombination as similar constants were obtained for both samples.…”
Section: Resultsmentioning
confidence: 63%
“…However, the excessive concentration of oxygen vacancies will become the recombination center of photo-generated carriers. 35 Therefore, it is observed that with further increasing the Nb doping amount, the PL intensity of BWO-Nb7 increases instead. The Fig.…”
Section: Photocatalysis Mechanismmentioning
confidence: 96%
“…17). Albeit small, this reduction of the uorescence lifetime, suggests that, relative to In 2 O 3 , single-site Bi atoms can increase the occurrence of competitive non-radiative relaxation processes in Bi x In 2-x O 3 [38][39][40] .…”
Section: The Actual Bulk Reaction Temperature For In 2 O 3 and Bi X Imentioning
confidence: 97%